Preparation of some new benzo[d]thiazole derivatives - Hoan, Duong Quoc; Anh Tuyet, Vu Thi; Duong, Le Thanh; Hien, Nguyen (Vietnam Journal of Chemistry, 2017)
In this work, four new benzo[d]thiazole derivatives were synthesized successfully from vanillin. Nitration of vanillin gave nitrovanillin followed by cyclization reaction with o-aminothiophenol under microwave irradiation in 4 minutes to give nitroaromatic compound 3. The reduction to convert the nitro group to amino group was optimized. It was found that Fe/ con. HCl in ethanol was the best condition for this case about both yield ( 95 %) and simple procedure to give compound 4 as a salt. Acetylation occurs at both phenolic hydroxyl group and amino group of the salt 4 to form N,O-acetyl compound 5. Under mild hydrolysis 5 produces N-acetyl compound 6. The structures of these compounds were established by IR, 1H and 13C NMR and mass spectral analyses. Keywords. benzo[d]thiazole, vanillin, reduction, microwave.